2015
DOI: 10.1515/hukin-2015-0024
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the Rope Skipping ‘STAR’ Programme for Schoolchildren

Abstract: Physical activity in children and adolescents is on a decline trend. To this end, we conducted a matched-pair randomized controlled trial to examine the effects of a 4-week STAR (School-based; Train-the-trainer; Accessibility of resources; Recreational) skipping programme. 1,386 schoolchildren from 20 primary and secondary schools were recruited. Schools were randomized into the experimental or wait-list control group. Participants self-reported their health-related quality of life using the KIDSCREEN-27. Acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 28 publications
2
64
0
Order By: Relevance
“…The inter‐rater reliability showed a percentage agreement of 84% across the 104 items ( k = 0.75). Most studies reported adequate results for each group and presented baseline characteristics separately for treatment groups for at least one outcome measure . Assessor blinding was reported in three studies , and in seven studies, all allocated subjects were analysed and not excluded because of missing data or non‐compliance .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inter‐rater reliability showed a percentage agreement of 84% across the 104 items ( k = 0.75). Most studies reported adequate results for each group and presented baseline characteristics separately for treatment groups for at least one outcome measure . Assessor blinding was reported in three studies , and in seven studies, all allocated subjects were analysed and not excluded because of missing data or non‐compliance .…”
Section: Resultsmentioning
confidence: 99%
“…The intervention duration ranged from 4 weeks to 28 months with a median duration of 9 months. Four studies utilized single‐component interventions to promote PA , while nine studies employed multiple intervention components .…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decades, numerous interventions have been introduced to motivate children and adolescents to eat more healthily and exercise more often, designed for different contexts, such as school (9)(10)(11), family home (12,13), sports club (14,15) and online (16,17). Interventions are of short (e.g.…”
mentioning
confidence: 99%
“…The most popular form of intervention involved modifying the built environment or providing additional equipment and supports for moderate-to-vigorous physical activity. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Other interventions deployed programming [44][45][46][47][48][49][50][51][52][53] or curriculum changes involving outdoor space [54][55][56][57][58][59][60][61][62][63] to promote physical activity. The concept of fostering spontaneous play in school and community-based settings was often an underlying component of these interventions.…”
Section: Physical Activitymentioning
confidence: 99%